Integrated Cyber Resilience Management in GIS: The Role of Norms DORA, NIS 2, NIST and ISO 27001 - Jerzy STANIK; Maciej KIEDROWICZ; Kazimierz WORWA (Communications of International Proceedings, 2025)
In the face of growing cyber threats, ensuring the resilience of geographic information systems (GIS) is becoming a priority for organizations around the world The aim of the article is to analyze cyber resilience management in geographic information systems (GIS) taking into account the role of DORA, NIS 2, NIST and ISO 27001 standards. It looked at how different security standards can be integrated to enhance the protection of GISs. This work brings a novel approach by integrating various compliance standards in the context of GIS, which has not been widely discussed in the literature so far. The practical value of the article lies in providing comprehensive recommendations for organizations that want to increase their resilience to cyber threats. The study used a literature review method, including an analysis of existing research, industry reports, and compliance standards, and a case study of the implementation of these standards in the selected GIS, assessing the effectiveness and challenges of their implementation. The main results indicate that the implementation of DORA, NIS 2, NIST and ISO 27001 significantly increases the level of security and operational resilience of GIS systems. These standards emphasize the importance of risk management, rapid incident response, and continuous improvement of security procedures. The article also provides specific recommendations for organizations, such as the implementation of risk management methodologies, regular audits, employee training, and monitoring compliance with standards. These findings are supported by case studies and empirical data, making them plausible and practical for cybersecurity professionals.
Keywords: integrated management; cybersecurity resilience; GIS systems; compliance standards.